Does change in thoracic impedance measured via defibrillator electrode pads accurately detect ventilation breaths in children? - Roberts, Kathryn; Srinivasan, Vijay; Niles, Dana E.; Eilevstjønn, Joar; Tyler, Lisa; Boyle, Lori; Bishnoi, Ram; Ferry, Susan; Nysæther, Jon; Stavland, Mette; Litman, Ronald S.; Helfaer, Mark; et al. (Resuscitation, 2010)
Resuscitation guidelines recommend rescue ventilations consist of tidal volumes 7–10 ml/kg. Changes in thoracic impedance (ΔTI) measured using defibrillator electrode pads to detect and guide rescue ventilations have not been studied in children. We hypothesized that ΔTI measured via standard anterior–apical (AA) position can accurately detect ventilations with volume >7 ml/kg in children. We also compared standard AA position with alternative anterior–posterior (AP) position. IRB-approved, prospective, observational study of sedated, subjects (6 months to 17 years) on conventional mechanical ventilation. Thoracic impedance (TI) was obtained via Philips MRx defibrillator with standard electrode pads for 5 min each in AA and AP positions. Ventilations were simultaneously measured by pneumotachometer (Novametrix CO 2SMO Plus). Twenty-eight subjects (median 4 years, IQR 1.7–9 years; median 16.3 kg, IQR 10.5–39 kg) were enrolled. Data were available for 21 episodes in AA position and 22 episodes in AP position, with paired AA and AP data available for 18. For ventilations with volume <7 ml/kg, the defibrillator algorithm detected 80.0% for both AA and AP ( p = 0.99). For ventilations ≥7 ml/kg, detection was 95.1% for AA and 95.7% for AP ( p = 0.38). Changes in thoracic impedance obtained via defibrillator pads can accurately detect ventilations above 7 ml/kg in stable, mechanically ventilated children, corresponding to rescue ventilations recommended during CPR. Both AA and AP pad positions were less sensitive to detect smaller volumes (<7 ml/kg) than higher volumes (≥7 ml/kg), suggesting that shallow ventilations during CPR might be missed. There were no differences in impedance measurements between standard AA pad position and commonly used alternative AP pad position.